QOLP-04. PILOT STUDY OF A VIDEOCONFERENCE-BASED PSYCHOLOGICAL INTERVENTION FOR FAMILY CAREGIVERS OF PATIENTS WITH MALIGNANT GLIOMAS. (9th November 2020) - Forst, Deborah; Mesa, Michelle; Kaslow-Zieve, Emilia; El-Jawahri, Areej; Greer, Joseph; Sereno, Isabella; Corveleyn, Amy; Anand, Maya; Landay, Sophia; Horenstein, Arielle; Temel, Jennifer; Jacobs, Jamie
Abstract: BACKGROUND: Caregivers of patients with malignant gliomas experience substantial anxiety symptoms while caring for someone with progressive neurological decline. Yet, interventions to reduce psychological distress and improve quality of life (QoL) in this caregiver population are lacking. METHODS: We conducted an open pilot study evaluating feasibility and acceptability of a cognitive behavioral therapy-based intervention for caregivers of patients with malignant gliomas with clinically significant anxiety (Generalized Anxiety Disorder [GAD-7] score ≥ 5). Caregivers participated in six videoconference sessions with a mental health provider. We defined the intervention as feasible if ≥ 70% of eligible caregivers enrolled and ≥ 70% of those enrolled completed ≥ 50% of sessions. We evaluated intervention acceptability in semi-structured interviews. Caregivers completed baseline and post-intervention surveys assessing anxiety and depression symptoms (Hospital Anxiety and Depression Scale), QoL (Caregiver Oncology Quality of Life Questionnaire), caregiving burden (Caregiver Reaction Assessment), self-efficacy (Lewis Cancer Self-Efficacy Scale), and perceived coping skills (Measure of Current Status-Part A). We explored post-intervention changes using paired t-tests. RESULTS: We obtained consent from 70.0% (21/30) of caregivers approached, of which 66.7% (14/21) had clinically significant anxiety and thus were eligible to participate (mean age=55.7 years, 64.3% female). Among enrolled caregivers, 71.4% (10/14) completed ≥ 50% of sessions. In semi-structured interviews, all participants found the intervention helpful and valued the ability to participate remotely via videoconference. Among caregivers who completed at least one session, 80.0% (8/10) completed all assessments and were included in analyses. Post-intervention, caregivers reported reduced anxiety symptoms (P=.02) and improved QoL (P=.03) and coping skills (P=.001). We found no significant change in depression, caregiving burden, or self-efficacy. CONCLUSION: Our videoconference-based intervention is feasible and acceptable to caregivers. Participants reported significant improvements in anxiety symptoms, quality of life, and coping skills post-intervention, supporting further investigation of the intervention in a randomized controlled trial.